Speaking the unspeakable : religion, misogyny, and the uncanny mother in Freud's cultural texts - Jonte-Pace, Diane E. (Diane Elizabeth), 1951- (Berkeley : University of California Press, 2001)
In this bold rereading of Freud's cultural texts, Diane Jonte-Pace uncovers an undeveloped 'counterthesis, ' one that repeatedly interrupts or subverts his well-known Oedipal masterplot.
Misogyny and Religion under Analysis -- The Counterthesis in "The Dream Book" and "A Religious Experience" -- Death, Mothers, and the Afterlife -- Jewishness and the (Un)Canny -- The Sources of Anti-Semitism -- Modernity, Melancholia, and the (In)Ability to Mourn.
Includes bibliographical references (pages 169-181) and index.
Print version record.
English.
JSTOR
Keywords: Freud, Sigmund, -- 1856-1939.; Freud, Sigmund, -- 1856-1939; Freud, Sigmund, -- 1856-1939; Freud, Sigmund, -- 1856-1939.; Freud, Sigmund; Psychoanalysis and religion; Feminist psychology; Psychoanalysis; Religion; Feminism; Psychoanalytic Theory; Religion; Feminism; Psychanalyse -- Aspect religieux; Psychologie féministe.; Psychanalyse; Religion; Féminisme.; psychoanalysis; religion (discipline); feminism; 77.14 psychoanalysis; 11.06 psychology of religion; PSYCHOLOGY -- Movements -- Psychoanalysis; RELIGION -- Judaism -- General; Religion; Psychoanalysis; Feminism; Feminist psychology; Psychoanalysis and religion; Psychoanalyse; Religion; Feminismus; Godsdienst; Vrouwenhaat; Moedercomplex